Pengaruh Kurs Dollar, Inflasi, Harga Terhadap Ekspor Kepiting Indonesia - Damayanthi, Made Dewi; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The fisheries subsector is second largest contributor to Indonesia's GDP in agricultural sector 2010-2013, supported by presence of export value of fishery products in 2008-2014 experiencing an increase. Crab exports rank third after shrimp and tuna export value. This study aims to determine the effect of US dollar exchange rate, foreign exchange, inflation, and prices on export value of crabs in Indonesia. This Research using time series data from 1980-2013 and analyzed by multiple linear regression. Results show exchange rate of US dollars, price of export crabs, inflation, and foreign exchange simultaneously have significant effect on crab exports. Partially the US dollar exchange rate and export crab prices have positive and significant effect on crab exports. Inflation have a negative and significant effect on crab exports. However, foreign exchange has negative and not significant effect on crab exports. Price of export crabs is has dominant effect on crab exports. keyword : crab exports, dollar exchange rate, inflation, prices